Traumatic complete pyloric transection following blunt abdominal trauma - Khac Thao Thai; Trong Hoe Nguyen; Thanh Son Le; Van Dan Nguyen; Doanh Hieu Tran (Medicine, 2026)
Rationale: Gastric rupture after blunt abdominal trauma is rare, and complex disruptions such as complete pyloric transection are exceptionally uncommon, having been described only in isolated case reports. Early diagnosis and timely surgical intervention are crucial to prevent septic complications resulting from peritoneal contamination. Patient concerns: A 31-year-old male presented with severe abdominal pain after a motorcycle collision following a heavy meal and alcohol intake. Diagnoses: The patient presented with agitation and impaired communication due to alcohol intoxication. Vital signs included a respiratory rate of 28 breaths/min, a pulse of 112 bpm, blood pressure of 110/60 mm Hg, and he was afebrile. Abdominal examination revealed epigastric bruising, mild distension, diffuse tenderness with epigastric predominance, abdominal guarding, and rebound tenderness suggestive of peritonitis. Whole-body contrast-enhanced computed tomography demonstrated pneumoperitoneum, extraluminal food spillage, and a clear discontinuity of the gastric wall, consistent with traumatic gastric rupture. Interventions: Emergency laparoscopy converted to laparotomy revealed complete pyloric transection, anterior antral rupture, and colonic seromuscular tears. The patient underwent two-thirds distal gastrectomy with Roux-en-Y reconstruction, extensive peritoneal lavage, and abdominal drainage. Outcomes: The postoperative course was favorable. Oral intake resumed on postoperative day 5, and the patient was discharged in stable condition on day 20. At the 30-day follow-up, he had normal eating and bowel habits, gained 3 kg, and endoscopy demonstrated a healed and patent anastomosis. Lessons: Whole-body contrast-enhanced computed tomography is highly valuable in the early evaluation of blunt polytrauma and may replace routine radiographs in centers with rapid pan-scan capability. However, when computed tomography is negative or inconclusive, operative decisions should still rely on clinical deterioration such as progressive abdominal distension and guarding. Complex gastric injuries, including complete pyloric transection, require prompt resection and restoration of gastrointestinal continuity to achieve favorable outcomes.